Sand Mineralogy Within the Bagnold Dunes, Gale Crater, as Observed In Situ and From Orbit. Issue 18 (27th September 2018) - Rampe, E. B.; Lapotre, M. G. A.; Bristow, T. F.; Arvidson, R. E.; Morris, R. V.; Achilles, C. N.; Weitz, C.; Blake, D. F.; Ming, D. W.; Morrison, S. M.; Vaniman, D. T.; Chipera, S. J.; et al.
Abstract: Curiosity investigated active eolian sands near linear dunes during Phase 2 of the Bagnold Dunes campaign in Gale crater, Mars. Ogunquit Beach, a sample scooped from a large‐ripple trough within the Mount Desert Island ripple field and delivered to the Chemistry and Mineralogy (CheMin) X‐ray diffraction instrument, is dominated by basaltic igneous minerals and X‐ray amorphous materials. CheMin mineralogy of the Gobabeb sample acquired at a large‐ripple crest on the Namib barchan dune during Phase 1 is similar to Ogunquit Beach. Ogunquit Beach, however, contains more plagioclase and Gobabeb contains more olivine. Compact Reconnaissance Imaging Spectrometer for Mars (CRISM)‐based estimates of mineralogy at the optical surface of Namib Dune and Mount Desert Island demonstrate that surface sands are enriched in olivine and depleted in plagioclase over Mount Desert Island relative to Namib Dune. Differences between CheMin‐derived and CRISM‐derived mineralogies suggest sorting by grain size on bedform to dune field scales. Crystal chemistry from CheMin suggests contributions from multiple igneous sources and the local bedrock. Plain Language Summary: Remote sensing data from orbit indicate that wind‐blown sands in the Bagnold Dune Field in Gale crater, Mars, are sorted by their composition. The Mars Science Laboratory Curiosity rover studied the Bagnold Dune Field at two locations to investigate the chemical and mineral composition of the sands and why they are sorted across the dune field. Data from Curiosity show distinct differences between the minerals in the upwind portion of the dune field compared to the downwind portion, but these differences are not the same as those observed from orbit. The scale and location of the sampling by Curiosity compared to orbiters explains the discrepancy between the two techniques. Results from both techniques suggest subtle differences in mineralogy within a single dune and across the dune field that can be explained by sorting from wind and contribution from the erosion of local bedrock. Key Points: The mineralogy of active eolian sands were measured by the Curiosity rover at two locations in the Bagnold Dune Field in Gale crater, Mars X‐ray diffraction data from the CheMin instrument of two sand samples indicate differences in plagioclase and olivine abundances The mineralogy derived from CheMin and CRISM can be used in concert to characterize sediment sorting and sources across the Bagnold Dunes